The surge in New University Presses and Academic-Led Publishing: an overview of a changing publishing ecology in the UK - Adema, Janneke; Stone, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
This article outlines the rise and development of New University Presses and Academic-Led Presses in the UK or publishing for the UK market. Based on the Jisc research project, Changing publishing ecologies: a landscape study of new university presses and academic-led publishing, commonalities between these two types of presses are identified to better assess their future needs and requirements. Based on this analysis, the article argues for the development of a publishing toolkit, for further research into the creation of a typology of presses and publishing initiatives, and for support with community building to help these initiatives grow and develop further, whilst promoting a more diverse publishing ecology.